A Multifunctional Self‐Assembled Monolayer for Highly Luminescent Pure‐Blue Quasi‐2D Perovskite Light‐Emitting Diodes. Issue 20 (8th September 2022) - Shin, Yun Seop; Ameen, Shahid; Oleiki, Elham; Yeop, Jiwoo; Lee, Youngwan; Javaid, Saqib; Park, Chan Beom; Song, Taehee; Yuk, Dohun; Jang, Hyungsu; Yoon, Yung Jin; Lee, Woojin; et al.
Abstract: Quasi‐2D perovskite materials have promise to unlock the full potential of blue perovskite light‐emitting diodes (PeLEDs). However, the efficiency of blue emissive PeLEDs still lags behind the green‐ and red‐emitting counterparts. Here, a multifunctional passivating molecule of (2‐(3, 6‐dichloro‐9 H ‐carbazol‐9‐yl)ethyl)phosphonic acid (36ClCzEPA) that can form a self‐assembled monolayer (SAM) on the indium tin oxide (ITO) electrode is reported. The 36ClCzEPA SAM facilitates hole injection by increasing the work function of ITO through the strong interfacial dipole layer formation at the interface between the perovskite emitter and the ITO electrode. Moreover, it allows a pure‐blue emission and reduces the exciton quenching of luminescence in the perovskite emitter considerably because of its neutral nature, compared to the commonly used acidic PEDOT:PSS. Furthermore, chlorine atoms in the 36ClCzEPA promote well‐ordered crystalline 2D perovskite phases and decrease interfacial trap‐assisted deactivation channels by interfacial passivation. These beneficial characteristics of the 36ClCzEPA SAM yield the excellent luminescence property of PeLEDs with a maximum luminance of 1253 cd m −2 and a peak external quantum efficiency of 4.80% at 473 nm. This work demonstrates that a well‐designed molecule forming an interfacial SAM can be an important component for enhancing the luminescence property of pure‐blue PeLEDs. Abstract : An effective interfacial engineering strategy to achieve highly luminescent blue perovskite light‐emitting diodes (PeLEDs) is demonstrated using the self‐assembled monolayer molecule of 36ClCzEPA which is utilized as hole injection layer. The interfacial dipole formation endows blue PeLEDs with low turn‐on voltage of 3.0 V and high luminance. With the strong PbCl orbital coupling, PeLEDs having well‐grown and thoroughly defect‐passivated perovskite emitter are successfully demonstrated.